Pengembangan instrumen evaluasi mata pelajaran biologi SMA kelas X di SMA Panjura Kota Malang - Tania Puspa Chandra; Triastono Imam Prasetyo; Agung (Universitas Negeri Malang, 2021)
2013 curriculum is a competency-based curriculum. An evaluation instrument is used to measure the students